Effect of Processing Parameters on Thickness of Columnar Structured Silicon Wafers Directly Grown from Silicon Melts - Jin-Seok Lee; Bo-Yun Jang; Young-Soo Ahn (International Journal of Photoenergy)
In order to obtain optimum growth conditions for desired thickness and more effective silicon feedstock usage, effects of processing parameters such as preheated substrate temperatures, time intervals, moving velocity of substrates, and Ar gas blowing rates on silicon ribbon thickness were investigated in the horizontal growth process. Most of the parameters strongly affected in the control of ribbon thickness with columnar grain structure depended on the solidification rate. The thickness of the silicon ribbon decreased with an increasing substrate temperature, decreasing time interval, and increasing moving velocity of the substrate. However, the blowing of Ar gas onto a liquid layer existing on the surface of solidified ribbon contributed to achieving smooth surface roughness but did not closely affect the change of ribbon thickness in the case of a blowing rate of ≥0.65 Nm3/h because the thickness of the solidified layer was already determined by the exit height of the reservoir.